Spatial Price Integration in Nepal - Kharel, Ram Sharan; Koirala, Tap Prasad (NRB Economic Review, 2011)
There is a large volume of literature documenting the analysis of spatial market integration based on individual commodity prices. This paper, instead, contributes to the literature by delineating the existence of spatial market integration using intra-regional price indices. In this context, we use monthly price indices for Kathmandu valley, Hill and the Terai region, which are the only available spatial indices in Nepal. Employing Johansens’ bi-variate cointegrating approach for the period from August 1995 to December 2010, we found a strong proposition of Law of One Price (LOP) across the region indicating the fact that spatial markets are highly integrated albeit speed of adjustment is rather slow. This may be due to the existence of oligopolistic pricing behaviour, carteling, asymmetric market information, and syndicate in the transportation system as discussed in various literatures.